Filter Cake Utilization as Filler of 15-15-15+5S Compound Fertilizer: Particle Size Distribution and Granule Crushing Strength Properties - Kasmadi Kasmadi; Budi Nugroho; Atang Sutandi; Syaiful Anwar (Reaktor, 2019)
Compound fertilizer which combining organic-inorganic materials need to be developed to improve the effectivness of fertilizers in the soil. Filter cake as a material has highly potential to be used as a filler in physical process granulation of compound fertilizer. In this study, the particle size distribution and granule crushing strength properties were tested using 15-15-15 + 5S fertilizer compound formula, which are varied in the filler composition and K sources. Potassium sources consisted of 2 (two) types of fertilizers i.e KCl and K2SO4. Filler composition as a binder in fertilizer granulation consists of 5 combination filter cake and clay ratios (60:40, 70:30, 80:20, 90:10 and 100:0). Granulation carried out by the granulation method using pan granulator of 2 kg/batch capacity, 23 rpm rotation speed and 50o pan slope. The results of the research showed that statistically the combination of filter cake and clay 70:30 had a size distribution and hardness of granules not significantly different from standard fertilizer (100% clay). Keywords: crushing strength; filler; filter cake; granulation; size distribution